Enhanced hydrogen-assisted cracking of 1,3,5-triisopropylbenzene over fibrous silica ZSM-5: Influence of co-surfactant during synthesis - N. A. A., Fatah; A. A., Jalil; M. L., Firmansyah; S., Triwahyono; H. D., Setiabudi; Vo, Dai-Viet N. (Elsevier Ltd, 2021)
In this study, unique fibrous silica ZSM-5 was successfully synthesized by using three type of alcohol possessing different alkyl-chain length as the co-surfactant. The effect of diverse co-surfactant was observed in the changes of physical properties, such as crystallinity, inter-dendrimer distances and pore properties. According to the IR and temperature programmed desorption of ammonia (NH3-TPD) analyses, all catalysts exhibited different acid strengths which could be triggered by the different amount of additional silica species. All catalysts exhibited high catalytic performance in the hydrocracking of 1,3,5-triisopropylbenzene due to the absence of diffusion limitation. However, FZSM5C3 exhibited the highest catalytic activity which corresponded to its high number of Brønsted acid sites. It was observed that different length of co-surfactant alkyl-chain has resulted in different degree of oil penetration into the microemulsion system which subsequently triggered in various inter-dendrimer distances and amount of incorporated silica species. Hence, the altered physicochemical properties led to the difference in catalytic performance due to the presence of different number of Brønsted acid sites.